Murcha da nogueira-pecã: estudo da relação planta-patógeno e antagonismo por Trichoderma spp. - Savian, Lucas Graciolli (2024)
The pecan tree [(Carya illinoinensis (Wangenh.) K. Koch] is a widely cultivated species. In RS, pecaniculture gained prominence due to its favorable climate and good financial return. However, the increase in diseases has negatively impacted the cultivation potential, with the pathogen Fusarium spp. being one of the main concerns. Fusarium wilt is an emerging disease, which is currently restricted to Brazil. Due to the polygaphus nature of the pathogen, there is potential for spread to other cultivation areas. In this context, understanding the The dynamics of host-pathogen interaction and efficient control methods are crucial to ensure the sustainability of the culture. The objective of this work was to study the pathosystem Carya illinoinensis six isolates pathogenic to pecan trees were used. In addition, isolates of Trichoderma spp. were obtained from rhizospheric soil, which were characterized morphologically and molecularly. Molecular identification was carried out using the regions of the Internal Transcribed Spacer (ITS), Elongation Factor 1-alpha (EF1-α) and the second largest subunit of RNA Polymerase II (RPB2). The biocontrol potential of the isolates was evaluated through culture pairing and volatile metabolite tests. Enzyme production was evaluated in vitro and the compounds produced by the pathogen in liquid media were identified. The plant x pathogen interaction was evaluated over time, at 30, 60 and 90 days after inoculation (d.a.i), through the production of: superoxide dismutase (SOD), guaiacol peroxidase (POD) and hydrogen peroxide (H2O2) . Lipid peroxidation was assessed by the value of malondialdehyde (MDA) present and the influence on development was assessed through measurements of height, duct diameter, fresh weight and dry mass. Six isolates of Trichoderma spp. were obtained, belonging to four species (Trichoderma asperelloides, T. virens, T. afroharzianum and T. hamatum), all efficient in the in vitro control of Fusarium spp. In the culture pairing test, the highest percentages of biocontrol were obtained by T. virens while for the volatile metabolites test T. asperelloides (AGCN05) stood out. Fusarium spp. produced extracellular enzymes in vitro, such as catalase, laccase, cellulase, caseinase, protease, lipase, polygalactoturonase, pectatolyase, and urease, with the exception of F. graminaearum that did not produce the lipase enzyme. The production of reactive oxygen species allowed us to observe that Fusarium spp. interacts differently with the host, as SOD, POD and H2O2 varied over time. The increasing value of lipid peroxidation indicated an inefficient response to control the pathogen. The greatest influence of the pathogen was observed at 90 d.a.i, with stagnation in plant development. DNA analysis made it possible to identify the species to which the Trichoderma isolates belong, presenting full potential for in vitro biocontrol. The production of a vast amount of enzymes by Fusarium spp. indicates different pathogenicity strategies adopted and enzymatic analysis highlights the complex dynamics of plant-pathogen interaction.